ANALISIS ATURAN PENGELOLAAN PROGRAM MODEL DESA KONSERVASI DI TAMAN NASIONAL GUNUNG RINJANI - Andi Chairil Ichsan (Jurnal Hutan Tropis, 2019)
This study aims to provide an overview of the rules used in the management of the conservation village model program in TNGR which has implications for the mechanism of regulating community rights in national park management. This research was designed using a case study approach. Research data was collected through several data collection instruments such as field observations, in-depth interviews, Focus Group Discussions (FGD), and literature studies. The results of this study indicate that changes in the control of rights over resources that are not well socialized and the unclear regulation of community rights in the use of resources in the implementation of MDK, have implications for the multi-interpretation of the rules of implementing MDK that causes MDK cannot become powerful social control tools. This study proves that although legally the management of national parks has high authority through the regulatory mandate inherent in its management system, it cannot be fully used as an effective instrument in controlling the actions of other parties towards the area. On the other hand, complex regulatory mechanisms at the constitutional level do not guarantee the effectiveness of program implementation in the field, if the regulation structure does not function as an incentive and runs simultaneously at all levels of regulation.